ANALISIS AKAD JUAL BELI MENGGUNAKAN SHOPEE PAYLATER DALAM PERSPEKTIF HUKUM ISLAM - Bilqis Salma Elysia; Muh Jufri Achmad (Gapenas Publisher, 2023)
Shopee pay later is a payment method that utilizes bailouts from related application companies. This Shopee paylater offers loan fund products with zero percent interest and no minimum transactions, and loans can be used to purchase various products at Shopee with a period of approximately 30 days. The size of the shopeepay later interest itself is ranging from 0% to 2.95% each month. The rules regarding interest which are considered small make shopee paylater an alternative that is used by the community in carrying out shopping activities so that their needs are met without money being paid in advance. This research was carried out as an attempt to look at the practice of shopee paylater credit by utilizing the shopee application and what is the Islamic perspective on the practice of shopee pay credit on the shopee marketplace. The research carried out was a type of field research, namely collecting data directly at the research location. Primary data obtained from interviews and secondary data obtained from books, theses, journals, fartwa, and so on are used. The findings of this study indicate that those who use the shopee register themselves to activate the shopee paylater, then when it is successfully activated, the shopee paylater can be used to carry out shopping activities. Based on Islamic law, the practice of shopee paylater credit on the shopee marketplace has two laws, namely mubah and haram. It was stated that it was mubah considering that the contract was carried out clearly, as evidenced by the existence of a contractual agreement made by the seller and the buyer when making an agreement and Kabul and giving an additional price to the shopee credit practice which was stated as a deferral price, and was determined unlawful because the additional costs referred to were usury which where usury is something that is forbidden in the long term of Islamic business ethics. Meanwhile, the shopee paylate credit policy implements an additional price of 2.95% to pay off bills for a certain period of time